Directed Gas Phase Formation of Silene (H2SiCH2). Issue 60 (4th October 2020) - Yang, Zhenghai; Doddipatla, Srinivas; He, Chao; Krasnoukhov, Vladislav S.; Azyazov, Valeriy N.; Mebel, Alexander M.; Kaiser, Ralf I.
Abstract: The silene molecule (H2 SiCH2 ; X 1 A1 ) has been synthesized under single collision conditions via the bimolecular gas phase reaction of ground state methylidyne radicals (CH) with silane (SiH4 ). Exploiting crossed molecular beams experiments augmented by high‐level electronic structure calculations, the elementary reaction commenced on the doublet surface through a barrierless insertion of the methylidyne radical into a silicon‐hydrogen bond forming the silylmethyl (CH2 SiH3 ; X 2 A′) complex followed by hydrogen migration to the methylsilyl radical (SiH2 CH3 ; X 2 A′). Both silylmethyl and methylsilyl intermediates undergo unimolecular hydrogen loss to silene (H2 SiCH2 ; X 1 A1 ). The exploration of the elementary reaction of methylidyne with silane delivers a unique view at the widely uncharted reaction dynamics and isomerization processes of the carbon–silicon system in the gas phase, which are noticeably different from those of the isovalent carbon system thus contributing to our knowledge on carbon silicon bond couplings at the molecular level. Abstract : Singlet silene (H2 SiCH2 ) is synthesized in the gas phase through carbon‐silicon bond linkage involving the barrierless elementary reaction of the methylidyne radical (CH) with silane (SiH4 ) under single collision conditions.